The relationship between gadolinium enhancement and [18 F]fluorothymidine uptake in brain lesions with the use of hybrid PET/MRI - Rohan, Tomáš; Hložanka, Petr; Dostál, Marek; Kopřivová, Tereza; Macek, Tomáš; Vybíhal, Václav; Martin, Hiroko Jeannette; Šprláková-Puková, Andrea; Keřkovský, Miloš (Cancer imaging, 2024)
BACKGROUND: To evaluate and compare the diagnostic power of [18F]FLT-PET with ceMRI in patients with brain tumours or other focal lesions. METHODS: 121 patients with suspected brain tumour or those after brain tumour surgery were enroled in this retrospective study (61 females, 60 males, mean age 37.3 years, range 1-80 years). All patients underwent [18F]FLT-PET/MRI with gadolinium contrast agent application. In 118 of these patients, a final diagnosis was made, verified by histopathology or by follow-up. Agreement between ceMRI and [18F]FLT-PET of the whole study group was established. Further, sensitivity and specificity of ceMRI and [18F]FLT-PET were calculated for differentiation of high-grade vs. low-grade tumours, high-grade vs. low-grade tumours together with non-tumour lesions and for differentiation of high-grade tumours from all other verified lesions. RESULTS: [18F]FLT-PET and ceMRI findings were concordant in 119 cases (98%). On closer analysis of a subset of 64 patients with verified gliomas, the sensitivity and specificity of both PET and ceMRI were identical (90% and 84%, respectively) for differentiating low-grade from high-grade tumours, if the contrast enhancement and [18F]FLT uptake were considered as hallmarks of high-grade tumour. For differentiation of high-grade tumours from low-grade tumours and lesions of nontumorous aetiology (e.g., inflammatory lesions or post-therapeutic changes) in a subgroup of 93 patients by visual evaluation, the sensitivity of both PET and ceMRI was 90%, whereas the specificity of PET was slightly higher (61%) compared to ceMRI (57%). By receiver operating characteristic analysis, the sensitivity and specificity were 82% and 74%, respectively, when the threshold of SUVmax in the tumour was set to 0.9 g/ml. CONCLUSION: We demonstrated a generally very high correlation of [18F]FLT accumulation with contrast enhancement visible on ceMRI and a comparable diagnostic yield in both modalities for differentiating high-grade tumours from low-grade tumours and lesions of other aetiology.
Keywords: Young Adult; Brain Neoplasms; Male; retrospektivní studie; Child, Preschool; dideoxynukleosidy; kontrastní látky; magnetická rezonanční tomografie; mladý dospělý; nádory mozku; Adolescent; Radiopharmaceuticals; Infant; Child; gadolinium; Positron-Emission Tomography; pozitronová emisní tomografie; dítě; Adult; [18F]FLT; Aged; dospělí; Brain tumour; mužské pohlaví; senioři; PET/MRI; Dideoxynucleosides; Multimodal Imaging; mladiství; předškolní dítě; senioři nad 80 let; radiofarmaka; lidé; ženské pohlaví; multimodální zobrazování; Contrast Media; Humans; Tumour-like lesions; Gadolinium; kojenec; senzitivita a specificita; Sensitivity and Specificity; Aged, 80 and over; High grade; Retrospective Studies; Magnetic Resonance Imaging; Female; Low grade; lidé středního věku; Middle Aged